DIGITAL COMMUNICATION LINK USING CONTINUOUSLY VARIABLE SLOPE DELTA MODULATOR CODE - Liew, Li Ching (Universiti Malaysia Sarawak (UNIMAS), 1998)
Undoubtedly, digital communication is playing the most important role in today's telecommunication system. This is due to digital communication possesses the benefit to transmit a large capacity of information, more secure, and better quality. By the way, the nature of information such as voice, video, and audio (music) is analogue signal. Therefore, in order to transmit the information into digital form (A/D) at the transmitting side, while at the receiving side, this digital signal needed to be converted back into analogue signal (D/A). Delta Modulation (DM) is one of the many ways to perform A/D and D/A conversion similar with PCM, and this is a type of PCM actually. However, DM is different from PCM on certain aspect, and this is one of the main topics to be discussed in this thesis. Eventhough DM does possesses some characteristic to en- ble it to be used on some application, it is however, does show some shortcomings. A s the result, Continuously Variable Slope Delta Modulation (CVSD) is introduced to overcome and minimize the shortcomings. Besides of being better from DM, CVSD circuit also more complexes, and it can be integrated into une single IC. This thesis also discusses more on the operating principles of the chosen CVSD codec. In doing my thesis, the most obvious problem I faced was the difficulty to find a suitable CVSD codec. As a result, this thesis report is merely a literature review, it may contain some mistakes or confusion, I apologize for that!